(untitled) (Revista Peruana de Investigación Educativa, 2021)
The study analyses the development of DDC digital teaching skills in the health emergency period per covid-19 during2020, distinguishing between the initial effect, post-first-time response strategies and tasks to consider for the 2021 school year. The work included teachers from 12 educational institutions in Lambayeque. Instruments such as the survey, in-depth interviews and focus groups were applied. Among the most relevant results are the presence of very innovative experiences that have followed the frustration and initial concern in the new technology-driven scenario, in addition, that the development of the CCD varies depending on the type of institution, the geographical area, the involvement of family members, access to technology and the level of institutional communication that favors collegiate work. However, it recognizes the teaching work to deal with the conditioning factors, especially the economics, emotionalis and social is. As for the technology, heterogeneities are expressed at the level of access gap, dominance and effective mastery of the same, the need to work much more on effective feedback is recognized from better control of the actions of the student and their families. In general, a comprehensive teacher training plan is required in digital skills that provides for the different areas that condition the process, demanding that the State make a greater commitment to promote the fulfilment of the stipulated goals for secondary education.